Phase 3 randomized, placebo-controlled study of galcanezumab in patients with chronic cluster headache: Results from 3-month double-blind treatment. (August 2020) - Dodick, David W; Goadsby, Peter J; Lucas, Christian; Jensen, Rigmor; Bardos, Jennifer N; Martinez, James M; Zhou, Chunmei; Aurora, Sheena K; Yang, Jyun Yan; Conley, Robert R; Oakes, Tina
Objective: To report efficacy and safety of galcanezumab in adults with chronic cluster headache. Background: Galcanezumab is a humanized monoclonal antibody that binds to calcitonin gene-related peptide and inhibits its biological activity. Methods: This study comprised a prospective baseline period, a 12-week double-blind, placebo-controlled treatment period, and a 52-week open-label period. Up to six protocol-specified concomitant preventive medications were allowed if patients were on a stable dose for 2 months prior to the prospective baseline period. Patients were randomized 1:1 to monthly subcutaneous galcanezumab (300 mg) or placebo. The primary endpoint was overall mean change from baseline in weekly attack frequency with galcanezumab compared to placebo. Key secondary endpoints were ≥50% response rate and percentage of patients meeting sustained response. Results from the double-blind treatment period are reported. Results: A total of 237 patients were randomized and treated (120 placebo; 117 galcanezumab). At baseline, the mean age was 45 years and 63% were using ≥1 preventive drug. The primary endpoint was not met; mean change in weekly attack frequency was −4.6 placebo versus −5.4 galcanezumab ( p  = 0.334). Key secondary endpoints also were not met. Injection site-related treatment-emergent adverse events were more common in the galcanezumab than the placebo group, with significantly more injection site erythema. Conclusion: Treatment with galcanezumab 300 mg did not achieve its primary and key secondary endpoints. This study underscores the potential distinct biology of cCH as well as the significant unmet need for safe, effective, and well-tolerated preventive treatment. The safety profile of galcanezumab in cCH is consistent with that observed in trials of episodic CH and migraine. Trial registration: NCT02438826;https://www.clinicaltrials.gov/ct2/show/NCT02438826 .